Students’ Metacognitive Strategies in Writing Argumentative Essay - Ratih Laily Nurjanah; Sri Waluyo (Metathesis: Journal of English Language, Literature, and Teaching, 2025)
Metacognitive strategies have demonstrated positive correlations with writing performance in educational contexts, particularly through planning, monitoring, and evaluating processes. However, existing research predominantly examines final writing products rather than students' actual strategy implementation patterns and perceptions during argumentative essay composition. This study investigated which metacognitive strategy aspects students most frequently employed and how they perceived these strategies in completing writing projects. Employing descriptive qualitative methodology, data were collected through questionnaires from 20 university students enrolled in a genre-based writing course, supplemented by interviews exploring their perceptions analyzed with thematic analysis. Findings revealed self-evaluation as the most consistently implemented aspect (95% for linguistic checking), while self-monitoring demonstrated the lowest and most variable utilization (45% for structural attention). Planning received moderate engagement, with reading before writing practiced by 85% of students, but visual planning by only 25%. Perceptual analysis uncovered a paradox: students recognized consultation and revision as essential yet perceived planning as temporally inefficient. This study concludes that metacognitive awareness does not automatically translate to strategic implementation, revealing a critical gap between declarative knowledge and procedural execution. These findings necessitate pedagogical shifts toward explicit self-monitoring training and demonstrate that metacognitive competence constitutes a fragmented, context-dependent construct requiring integrated instructional approaches beyond isolated strategy awareness.